Skrining Kesehatan Kulit dengan Penilaian Kadar Air dan Minyak pada Kelompok Usia Produktif di Sekolah Kalam Kudus II, Duri Kosambi - Sidarta, Erick; Averina, Friliesa; Herdiman, Alicia; Destra, Edwin (Institut Teknologi dan Bisnis Semarang, 2024)
Skin health, as the body's largest organ, is an important aspect of health. It plays an important role such as: protection against pathogens, regulating temperature, and preventing fluid loss. Internal factors such as genetics, hormones, and general health, as well as external factors such as UV exposure, pollution, skin care habits, and diet, influence skin health. The aim of this activity is to increase health awareness and provide education about the importance of maintaining healthy skin. Community service activities were done at Kalam Kudus II High School using the PDCA (Plan-Do-Check-Act) method. At the planning stage, skin health problems were identified and educational activity plans were drawn up. Implementation includes health seminars, individual consultation sessions, and skin examinations using a skin analyzer to assess the oil and water content of the skin. Evaluation was carried out by collecting feedback from participants, and follow-up actions were prepared based on the evaluation results. A total of 68 participants took part in this activity. It was observed that in 18-35 year age group, skin conditions were more stable compared to the 36-50 year age group. In which the latter was starting to show signs of skin aging. This also shown in the 51-64 year age group whom experiencing dry skin and other skin problems more often.